Two hemocyte populations in Triatoma infestans: ultrastructural and lectin-binding characterization - Hypsa, V; Grubhoffer, L (Folia parasitologica, 1997)
Two distinct hemocyte populations are determined in the hemolymph of the triatomine bug Triatoma infestans Klug, oenocytoids and plasmatocytes, and their independent origin from separate stem cells is shown. Both hemocyte populations differ considerably in their morphology, ultrastructure and lectin-binding properties. While oenocytoids are quite uniform with easily definable cells which do not to bind any assayed lectin, the plasmatocytes are a very polymorphic population possessing several morphological types and displaying a positive reactivity with lectins.
Keywords: Protein Binding; hemocyty; Animals; Lectins; lektiny; Triatoma; zvířata; Hemocytes; vazba proteinů